Repatriating Polanyi: Market Society in the Visegrad States - Hann, Chris (Central European University Press, 2019)
Karl Polanyi’s “substantivist” critique of market society has renewed topicality in the era of neoliberal globalization. Polanyi (1886–1964) is popular among critical theorists and radical political economists, but also with ecological activists, anti-globalization campaigners and all who sense that ongoing financial turmoil is symptomatic of a deeper crisis threatening the compatibility of capitalism and democracy. The author reclaims the polymath Karl Polanyi for contemporary anthropology, especially economic anthropology. The book furthermore takes his ideas back to Central Europe, where he grew up. The Polanyian approach is applied to the communist economy, with particular reference to the “market socialist” economy which evolved under János Kádár in Hungary. The same lens is used to investigate the consequences of the demise of communist power since 1990, primarily on the basis of ethnographic investigations in Hungary and South-East Poland. Stretching the discussion on Polanyi’s great transformation – for which there is considerable international interest – in the context of neoliberalization onto the concept of Eurasia, and then bringing this into conversation with the rise of neo-nationalism in Hungary and Poland and beyond as the form that the great transformation is currently taking in the region, relates Hann’s work powerfully to the current political turbulence.
Keywords: Hungary; Poland; communist economy; economic history; market socialist economy; neo-nationalism; political economy

A Handbook of Economic Anthropology, Second Edition - Carrier, James G. (Edward Elgar Publishing, 2012)
Acclaim for the first edition: 'The volume is a remarkable contribution to economic anthropology and will no doubt be a fundamental tool for students, scholars, and experts in the sub-discipline.' _ Mao Mollona, Journal of the Royal Anthropologica
Keywords: business & economics; cultural anthropology; cultural policy; economic anthropology; macroeconomics; political science; popular culture; public policy; social science

Economic Anthropology - Hann, Chris; Hart, Keith (Polity, 2011)
This book is a new introduction to the history and practice of economic anthropology by two leading authors in the field. They show that anthropologists have contributed to understanding the three great questions of modern economic history: development, socialism and one-world capitalism. In doing so, they connect economic anthropology to its roots in Western philosophy, social theory and world history. Up to the Second World War anthropologists tried and failed to interest economists in their exotic findings. They then launched a vigorous debate over whether an approach taken from economics was appropriate to the study of non-industrial economies. Since the 1970s, they have developed a critique of capitalism based on studying it at home as well as abroad. The authors aim to rejuvenate economic anthropology as a humanistic project at a time when the global financial crisis has undermined confidence in free market economics. They argue for the continued relevance of predecessors such as Marcel Mauss and Karl Polanyi, while offering an incisive review of recent work in this field. Economic Anthropology is an excellent introduction for social science students at all levels, and it presents general readers with a challenging perspective on the world economy today.Selected by Choice as a 2013 Outstanding Academic Title
Keywords: cultural anthropology; economic anthropology; social anthropology; sociology - general

Market and Society: The Great Transformation Today - Hann, Chris; Hart, Keith (Cambridge University Press, 2009)
Karl Polanyi's 1944 book, The Great Transformation, offered a radical critique of how the market system has affected society and humanity since the industrial revolution. This volume brings together contributions from distinguished scholars in economic anthropology, sociology and political economy to consider Polanyi's theories in the light of circumstances today, when the relationship between market and society has again become a focus of intense political and scientific debate. It demonstrates the relevance of Polanyi's ideas to various theoretical traditions in the social sciences and provides perspectives on topics such as money, risk, work and the family. The case studies present materials from around the world, including Britain, China, India, Jamaica and Nigeria. Like Polanyi's original work, the critical engagement of these essays will be of interest to a wide readership.
Keywords: anthropology - general; business & economics; economic history; economic theory; sociology - general

Against the Law: Labor Protests in China’s Rustbelt and Sunbelt - Lee, Ching Kwan (University of California Press, 2007)
This study opens a critical perspective on the slow death of socialism and the rebirth of capitalism in the world's most dynamic and populous country. Based on remarkable fieldwork and extensive interviews in Chinese textile, apparel, machinery, and household appliance factories, Against the Law finds a rising tide of labor unrest mostly hidden from the world's attention. Providing a broad political and economic analysis of this labor struggle together with fine-grained ethnographic detail, the book portrays the Chinese working class as workers' stories unfold in bankrupt state factories and global sweatshops, in crowded dormitories and remote villages, at street protests as well as in quiet disenchantment with the corrupt officialdom and the fledgling legal system.
Keywords: China; cultural anthropology; double movement; fictitious commodities; labour; social anthropology